1990
DOI: 10.2527/1990.68103350x
|View full text |Cite
|
Sign up to set email alerts
|

The nutritive value for sheep of quackgrass and timothy hays harvested at two stages of growth.

Abstract: Thirty-two wethers were used to compare the nutritive value of Climax timothy (Phleum pratense L.) and quackgrass (Agropyron repens L. Beauv.) harvested at two stages of maturity, joint and early heading, and fed as hay. Crude protein was higher for quackgrass than for timothy (P less than .01). As maturity advanced, CP decreased (P less than .01), but NDF and ADL increased (P less than .01). Dry matter intake was similar between species but decreased by 8% with increasing maturity (P less than .01). Intake of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…The highest DM intake (g/LWkg 0.75 /day) and digestibility of DM and NFE in oat hay sample‐2 reflected the lowest CF, OCW and Ob, but the highest NFE and OCC concentrations in the diet. In contrast, the highest digestibility of CP in oat hay sample‐1 was contributed to by the highest CP concentrations in the hay, which is supported by the results of Christen et al . (1990).…”
Section: Discussionsupporting
confidence: 79%
“…The highest DM intake (g/LWkg 0.75 /day) and digestibility of DM and NFE in oat hay sample‐2 reflected the lowest CF, OCW and Ob, but the highest NFE and OCC concentrations in the diet. In contrast, the highest digestibility of CP in oat hay sample‐1 was contributed to by the highest CP concentrations in the hay, which is supported by the results of Christen et al . (1990).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, in our study, the dry matter yields of the first and second pasture were higher than the reported dry matter yields. We also note that a previous report stated that the productivity of Quackgrass, the dominant weed in the researched area, was lower than that of Timothy [27,28]. Still, in our study, we observed that there was no significant difference in dry matter yield between the Timothy and Quackgrass-dominated pastures in terms of quantity.…”
Section: Dry Matter Yield and Qualitycontrasting
confidence: 53%
“…Increasing water stress, for example, decreases plant maturity, resulting in a better quality forage (Halim et al 1989 Mertens (1973) and Waldo (1986). Although the use of CF has lost popularity because of its rather ill-defined composition, this fraction is often correlated with DM intake (Seoane 1982;Christen et al 1990). Dry matter solubility was also correlated with DM intake, thus supporting the observations reported by Donefer et al (1963) and (Crampton et al 1957 Soest (1961), was developed from data from all forages, using the regression equations that estimate NDF digestibility (Table 6) and digestible cell content (Table 7) (Reid et al 1988).…”
mentioning
confidence: 99%